Effect of ethylene released from Ethrel in alkaline medium on banana (Musa spp.) fruit ripening - Arabi, Mamoun; Abu-Goukh, Abu-Bakr (المجلة الزراعية; مجلد 17 عدد 1 (2019), 2019)
The effect of ethylene gas, released from Ethrel in alkaline medium, on banana fruit ripening was evaluated. ‘Dwarf Cavendish‘ banana fruits were obtained from a private orchard in Sinja, 400 kilometers south of Khartoum. The fruits were harvested at the ’full three quarters‘ maturity stage and transported to the laboratory at the Department of Horticulture, Faculty of Agriculture, University of Khartoum. They were washed with water to remove latex and dust, treated with 10% sodium hypochlorite as a disinfectant and air-dried. The fruits were treated with ethylene gas released from Ethrel at 0 (control), 250, 500 and 1000 ppm for 24 hrs. in hermetically sealed 20 l plastic chambers. Calculated amount of Ethrel that release the desired ethylene gas concentration was added to a beaker containing 15 ml of 40% Na OH in each chamber and immediately closed. After 24 hrs., the chambers were opened and fruits were placed in carton boxes lined with perforated polyethylene films and kept at 18±1˚C and 80%-85% relative humidity. Treatments with ethylene gas released from Ethrel at 250, 500, and 1000 ppm significantly accelerated fruit ripening, the higher the concentration the more was the effect. Depending on concentration, ripening was 2-5 days earlier in the treated fruits, compared with the control. The untreated fruits reached the climacteric peak of respiration after 10 days. Ethylene treatment at 250, 500, and 1000 ppm significantly accelerated the onset of the climacteric peak by 2, 4 and 5 days, respectively, compared with the untreated fruits. The effect of ethylene released from Ethrel on banana fruit ripening was also indicated by increased peel color development, total soluble solids (TSS), total and reducing sugars accumulation and enhanced fruit softening and weight loss.   قُــوم تأثيـر غــاز الٳثليـن المنبعث من الٳثريــل فى وســط قلــوى على ٳنضاج  ثمــار المــوز. وفــرت ثمــار المــوز من صنف ‘دوارف كافندش’ من مزرعـة خاصة  فى منطقة سنجة، 400 كيلومتراً جنوب الخرطوم. حصدت الثمار فى مرحلة ‘ثلاثة أرباع ممتلئة’ من ٳكتمال النمو وتم ترحيلها ٳلى المعمل فى قسم البساتين، بكلية الزراعة، جامعة الخرطوم. غسلت الثمار بالماء لٳزالة العصارة والأتربة وعوملت بهيبوكلوريت الصوديوم (10%) كمطهر ثم  جففت الثمار بازالة الماء العالق بها بواسطة تيار من الهواء. عوملت الثمار بغاز الٳثيلين المنبعث من الٳثريل بتركيز صفر (شاهد) و 250 و500 و1000 جزء فى المليون لمدة 24 ساعة فى حاويات بلاستيكية محكمة الٳغلاق سعة 20 لتراً. أضيفت الكميات المحسوبة من الٳثريل التى تفرز التركيزات المطلوبة الى 15 ملى ليتر من هيدروكسيد الصوديوم (40%) وضعت فى كؤوس زجاجية داخل الحاويات واغلقت الحاويات مباشرة بعد ذلك. بعد 24 ساعة من المعاملة  فتحت الحاويات ووضعت الثمار فى صناديق من الكرتون مبطنة بشرائح البولى ٳثيلين المثقب وحفظت على درجة حرارة 18±1 ˚م ورطوبة نسبية 80% - 85%. أدت المعاملة بالٳثيلين المنبعث من الٳثريل معنوياً ٳلى الٳسراع  بنضج ثمار الموز، وكان التركيز الأعلى أكثر فعالية. كان الٳنضاج أسرع فى الثمار المعاملة بمقدار 5-2 أيام حسب التركيز، مقارنة بالثمار غير المعاملة. أدت المعاملة بغاز الٳثيلين المنبعث من الإثريل معنوياً لتسريع وصول الثمار إلى ذروة التنفس. فقد وصلت الثمار غير المعاملة ٳلى ذروة التنفس، بعد 10 أيــام، وقد تسارع معنوياً وصول الثمار المعاملة بغاز الٳثيلين المنبعث من الٳثريل بتركيز 250 و500 و1000 جزء فى المليون ٳلى ذروة التنفس 2 و4 و5 أيــام، على التوالى، مقارنة بالثمار غير المعاملة. كما انعكس تأثير المعاملة بغاز الٳثيلين، المنبعث من الٳثريل، فى ٳنضاج ثمار الموز فى الزيادة فى تلوين القشرة الخارجية للثمار وتراكم المواد الصلبة الكلية الذائبة والسكريات الكلية  والمختزلة والٳسراع  بليونة لب الثمار وفقدان الوزن فيها.